Revealing the Form of Constraints and Switched Points in Cewek Smart #2 - Nurasiah Amin; Abdul Muhid; Hilda Hastuti (Humanitatis : Journal of Language and Literature, 2022)
This reserach was done to reveal the dominant form of Constraints and Switched Points of code switching usage in Cewek Smart #2 book by Ria Fariana, which the data is taken from chapter 1 to chapter 6 of total 53 pages. To reveal the form of constraints and switched points of code switching, it was considered to use theory by Poplack about code switching, and the data were analyzed by using a qualitative method. This current research shows that there were 21 forms of constraints and switched points and there are 6 dominant forms used in the book of Cewek Smart #2, namely between Adverb and VP, between NP and zero marking (-), between VP and zero marking (-), between Independent Clause and Zero Marking (-), Between PP and and Zero Marking (-), Between Conj. and zero marking (-). in the book of Cewek Smart #2.